2022
DOI: 10.1371/journal.pone.0266932
|View full text |Cite
|
Sign up to set email alerts
|

Use of WhatsApp messaging technology to strengthen obstetric referrals in the Greater Accra Region, Ghana: Findings from a feasibility study

Abstract: In Ghana, the high-risk obstetric referral system is inadequate. Delay is common and patients often arrive to receiving hospitals in compromised states. An effective referral system should include an adequately resourced referral hospital, communication across sectors, accountability, transport, monitoring capability and policy support, which are currently lacking. A pilot program was undertaken to facilitate communication between hospital staffs. Additionally, data was collected to better understand and chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…While limited novel interventions aimed to reduce the "third delay" and improve obstetric triage within facilities have been piloted in some LMIC settings, few have proposed interventions to encompass care delivery from the pre-hospital to facility setting [20][21][22]. A feasibility study in Ghana utilized WhatsApp as a platform for referring obstetric patients to higher care centers, with findings demonstrating usability by various health care professionals from different types of health centers, long variations in arrival time to facility for obstetric patients, and decreased arrival time when patients were accompanied by midwives [23]. Combining our findings with this pilot program suggest that a WAT-RT System, when assessed and implemented with appropriate adaptation, could provide a platform for obstetric triage in West Africa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While limited novel interventions aimed to reduce the "third delay" and improve obstetric triage within facilities have been piloted in some LMIC settings, few have proposed interventions to encompass care delivery from the pre-hospital to facility setting [20][21][22]. A feasibility study in Ghana utilized WhatsApp as a platform for referring obstetric patients to higher care centers, with findings demonstrating usability by various health care professionals from different types of health centers, long variations in arrival time to facility for obstetric patients, and decreased arrival time when patients were accompanied by midwives [23]. Combining our findings with this pilot program suggest that a WAT-RT System, when assessed and implemented with appropriate adaptation, could provide a platform for obstetric triage in West Africa.…”
Section: Discussionmentioning
confidence: 99%
“…WhatsApp, a commonly used mobile communication platform throughout much of the world, including SSA, has demonstrated usability as an mHealth intervention. Piloted in studies covering infectious disease [14], medical education and research [15,16], and preventive medicine [17], WhatsApp holds promise as a commonly used, low-cost, and secure data messaging system but has been underexplored as a potential platform to address delays in obstetric care [18]. Midwives and community health assistants (CHAs) serve as the frontline providers for obstetric care in rural Liberia.…”
Section: Introductionmentioning
confidence: 99%
“…A study showed statistically significant improvements, with a mean increase in knowledge from 11.21 to 13.68 following a health education intervention focusing on noncommunicable diseases via digital media, i.e., WhatsApp [24]. The adoption of elearning for training healthcare professionals has surged exponentially, with several studies affirming its effectiveness [25,26,27,28,29]. Furthermore, using social media and mHealth apps in pregnancy care has shown considerable effectiveness, yielding moderate to large effect sizes in enhancing maternal health and knowledge among healthcare professionals [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…WhatsApp, one of the most popular communication platforms worldwide has been examined as a potential means to streamline the obstetric referral process between communities, RHFs, and hospitals. [9][10][11] Several feasibility and acceptability studies conducted in Ghana and Liberia found that the use of WhatsApp for obstetric referral is feasible and acceptable among community health workers, nurses, and midwives. [9][10][11] Building upon these studies, this study piloted a mobile obstetric emergency system (MORES) using the free WhatsApp platform as an obstetric referral intervention examining the association between the implementation of the MORES intervention and transfer times, maternal outcome, and newborn outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…WhatsApp, one of the most popular communication platforms worldwide has been examined as a potential means to streamline the obstetric referral process between communities, RHFs, and hospitals 9‐11 . Several feasibility and acceptability studies conducted in Ghana and Liberia found that the use of WhatsApp for obstetric referral is feasible and acceptable among community health workers, nurses, and midwives 9‐11 .…”
Section: Introductionmentioning
confidence: 99%